1993
DOI: 10.1002/art.1790060104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a walking program on gait characteristics in patients with osteoarthritis

Abstract: This paper reports the results of a study of the gait of 102 patients with osteoarthritis of theknee. Functional status was measured by a 6‐min test of walking distance; the stride characteristics associated with the walk test were assessed. Stride characteristics were measured by a StrideAnalyzer. Patients were randomized to an 8‐week educational and walking program (the intervention group) or to a weekly telephone survey (the control group). The intervention group patients had a 15% increase in walking dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 9 publications
3
49
0
1
Order By: Relevance
“…As in our study, other studies have also found associations between capability variables (6-minute gait distance, index of ambulatory independence, SF-36 scores, WOMAC scores, gait speed, stride length, stair ascent duration), on the one hand, and measures of locomotor ability, on the other hand, in persons with OA (44,53,110,165), TKA (133), and in elderly people (42,139,145,146,159). All these capability variables, except stride length, have previously been used in regression models predicting locomotor ability (133,139,143) and self-perceived functional ability (6,20,103,145,146) in various populations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As in our study, other studies have also found associations between capability variables (6-minute gait distance, index of ambulatory independence, SF-36 scores, WOMAC scores, gait speed, stride length, stair ascent duration), on the one hand, and measures of locomotor ability, on the other hand, in persons with OA (44,53,110,165), TKA (133), and in elderly people (42,139,145,146,159). All these capability variables, except stride length, have previously been used in regression models predicting locomotor ability (133,139,143) and self-perceived functional ability (6,20,103,145,146) in various populations.…”
Section: Discussionsupporting
confidence: 89%
“…Construct and concurrent validity of the 6-minute gait test has been extensively demonstrated in populations with cardiopulmonary problems (41,44 -51). In populations with OA, a good concurrent validity was also shown with respiratory measures (52,53), knee extensor strength (53), stride characteristics (44), and timed up and go (54). Moreover, the predictive ability of the 6-minute gait test was studied.…”
Section: Predictors Of Locomotor Ability Two Months After Tkamentioning
confidence: 99%
“…The effectiveness of regular exercise in the management of pain and improvement of physical function has been established in patients with knee OA 3,4,[16][17][18] . In the present study, the stretching group showed significantly greater improvement in S-ROM than the control group and the mean percentage change was about 9%.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that regular exercise, such as muscle exercise and walking, is beneficial for the management of pain and improvement of physical function in patients with knee OA 3,4) . Although home-based exercises have advantages over clinicor hospital-based exercises because they are inexpensive and easy to perform, there are concerns about long-term implementation of home-exercise regimens.…”
Section: Introductionmentioning
confidence: 99%
“…They walked 72% before TKA and 58% 2 months after TKA of the control values. Validity, reliability, and responsiveness of the 6 minute walk test have been reported in patients with rheumatoid arthritis and OA (Guyatt et al 1985, Peterson et al 1993, Price et al 1988. Reduced functional capacity of people with knee OA is a major characteristic of the disease and distance covered in 6 minute appears to be a good index of functional ability.…”
Section: Measures Of Functional Abilitymentioning
confidence: 99%